P805 Clinical and echocardiographic characteristics of Polish patients with Eisenmenger Syndrome - results of a snapshot registry. (17th January 2020) - Mamzer-Dachnowska, A; Kopec, G; Kusmierczyk, B; Skowron, W; Mroczek, E; Lewicka, E; Kaminski, K; Karasek, D; Mularek-Kubzdela, T; Mizia-Stec, K; Kurzyna, M; Gasior, Z; et al.
Abstract: The first national registry of patients (pts) with PAH-CHD, predominantly with Eisenmenger Syndrome (ES), treated within national program was conducted. We studied clinical and echocardiographic characteristics of a group of adult patients including current therapy profile and mortality. A multicenter observational study (snapshot registry) was conducted under auspices of Polish Cardiac Society, including pts with PAH-CHD, identified in centers, that treated > 5 pts in the first 10 years of therapeutic program (2008-2018). This analysis included 322 pts (70 deceased), mean age 42 ± 2 years, 65% females. The registry included patients meeting the criteria of the Eisenmenger syndrome in echocardiography (right-left or aligned leak). The living patients were divided into 2 groups: Gr.1 (n = 227) – uncorrected and Gr.2 (n = 25) - after correction of the heart disease. The average age in Gr.1 was 40 ± 2 years, in Gr.2 40 ± 6 years. The majority were women (68% and 62%). There was no significant differences for mean duration of treatment in groups: 60 ± 12 months vs. 66 ± 6 months (p = 0.42). Both groups didn't differ in terms of clinical data, i.e. 6MWT 417 ± 50 m vs. 384 ± 15 m;p = 0.15, NT-proBNP level 869 ± 470 pg/ml vs. 901 ± 212 pg/ml;p = 0.57. There was no significant differences for mean LVd in groups: 41, 24 mm [12-82] vs. 44, 25 mm [30-55]. Mean LVEF was good (60% in gr.1 vs. 57% in gr.2). Mean TAPSE was slightly better in Gr.1: 19, 36 mm vs. 17, 09 mm. Pericardial effusion were present in almost 15% pts from Gr.1 and less than 1% pts from Gr.2. Pts after correction were mostly in the II WHO FC, and those uncorrected in the II/III WHO FC. Pts from Gr.2 were more likely to receive polytherapy (60% vs. 47%). ERA were the most commonly used (near 90%). The most common heart defect was VSD (46% in Gr.1 vs. 32% in Gr.2). Mortality was 22% in entire period, i.e. annual mortality rate of 2.2%. In the group of dead pts women accounted for 74%, the average age was 49 ± 4 years and mean length of treatment was 42 ± 13 months. About 9% of pts from this group had heart defect correction in the past. Monotherapy (66%) predominated among the deceased, mainly using ERA (77%). Pts receiving combination therapy had a longer survival (p = 0.04). It isn't known whether this result confirms the greater effectiveness of such treatment, as some patients couldn't wait until the polytherapy became possible within the framework of the Drug Program. Among the deceased, the most common heart disease was ASD (30%), slightly less VSD (29%). In this first national snapshot registry we documented improving prognosis in PAH-CHD under specific therapies. No differences were present in the length of therapy, clinical data and quality of life depending on whether or not correction surgery was performed. Post-correction pts more often received a polytherapy. The annual mortality in this population is small estimated just over 2%. Targeted combination therapy may contribute to better survival.